Family and School Factors and Headache Prevalence - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The prevalence of headache in children aged 7-16 years, representing districts of the city of Goteborg with socioeconomic, family, and school variables, is reported from Sahlgrenska Hospital, Goteborg, Sweden.